NASIONALISME VAKSIN SEBAGAI PRAKTIK NEOMERKANTILISME: ANALISA STUDI EKONOMI POLITIK INTERNASIONAL - Wildan Faisol; Nizar Umar (UIN ALAUDDIN MAKASSAR, 2022)
At first the health issue was the main task for each country to each of its people. But now the health issue has become part of a global issue whose dynamics have become the focus of various international collaborations. In this case, the Covid-19 pandemic, which has been running for more than a year in the world since the outbreak in China, has now found various innovations regarding vaccines to prevent the spread of Covid-19. This innovation in the production of the Covid-19 vaccine is controlled by various international pharmaceutical companies. However, in terms of the distribution of the Covid-19 vaccine globally, it appears that several developed countries have implemented protectionist approach with the aim of securing the availability of the Covid-19 vaccine for their domestic needs. In this study, the author would like to explain that the Vaccine Nationalism practices that occurred during the Covid 19 pandemic era were a policy development from the perspective of Neomercantilism in the study of international political economy. This article was written using a qualitative research method with a descriptive type of research. The results of this study explain that the practice of vaccine nationalism is the steps taken by developed countries in treating vaccines as a strategic commodity, not as a global public commodity. Developing and less developed countries have the potential to experience barriers to accessing the availability of vaccines in dealing with the Covid-19 pandemic.